2017
DOI: 10.1002/2017gl074416
|View full text |Cite
|
Sign up to set email alerts
|

Newly Discovered Ring‐Moat Dome Structures in the Lunar Maria: Possible Origins and Implications

Abstract: We report on a newly discovered morphological feature on the lunar surface, here named Ring‐Moat Dome Structure (RMDS). These low domes (a few meters to ~20 m height with slopes <5°) are typically surrounded by narrow annular depressions or moats. We mapped about 2,600 RMDSs in the lunar maria with diameters ranging from tens to hundreds of meters. Four candidate hypotheses for their origin involving volcanism are considered. We currently favor a mechanism for the formation of the RMDS related to modification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
58
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(66 citation statements)
references
References 40 publications
7
58
1
Order By: Relevance
“…Figure 10b exhibits three RMDSs showing a complex spatial relationship with each other. The largest RMDS is about 550 m in diameter and tangent to a smaller one (~220 m) to its south, which appears as a satellite of the larger RMDS, and this arrangement was previously reported as dumbbell and short chain patterns by Zhang et al (2017). A small RMDS or lava dome (yellow arrow) is observed on the western flank of the largest RMDS, which partially superposes an ~500 m diameter impact crater to its northeast.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…Figure 10b exhibits three RMDSs showing a complex spatial relationship with each other. The largest RMDS is about 550 m in diameter and tangent to a smaller one (~220 m) to its south, which appears as a satellite of the larger RMDS, and this arrangement was previously reported as dumbbell and short chain patterns by Zhang et al (2017). A small RMDS or lava dome (yellow arrow) is observed on the western flank of the largest RMDS, which partially superposes an ~500 m diameter impact crater to its northeast.…”
Section: Resultssupporting
confidence: 72%
“…Some RMDSs are found adjacent to what appear to be morphologically mature and generally circular depressions (white arrows, Figure 8a) or even to partially superpose them (Basilevsky et al, 2019; Zhang et al, 2017). In the examples shown here, the mature craters partially superposed by RMDSs (Figures11a and 11b) usually exhibit a general symmetric profile of the cavity along the line cutting through superposed RMDSs.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, bright boulders are usually present within the marginal ring of topographic lows (Figure c). These moat‐mound structures share many morphological similarities with the so‐called ring‐moat dome structures (Zhang et al, ). We interpret these unusual central uplifted structures as possible miniature analogs of Ina mound units, and the marginal ring of lows analogous to the moats frequently occurring along the edges of Ina mounds, where fresh boulders are also often observed (Figure c).…”
Section: Interior Of Inamentioning
confidence: 95%
“…On a timescale of weeks, the resulting compound flows would cool, and the concentration of volatiles into the residual liquid as crystallization occurred would lead to second boiling, with the resulting new population of gas bubbles causing a further, possibly extensive, inflation episode. Extrusion of the resulting magmatic foam through cracks in the lava crust may be an explanation of the ring moat dome structures (RMDSs; Zhang et al, ) found in large numbers on many mare flows.…”
Section: Evolution Of a Typical Lunar Basaltic Eruption: The Four Phasesmentioning
confidence: 99%
“…In other cases the foam intrusion raises the crust of the crater lake and overflows onto the upper flanks, where partial collapse of the foam produces another type of IMP, such as those on the flanks of Cauchy 5 (Qiao et al, ). Similar features occur on the floor of the Hyginus collapse caldera (Braden et al, ). RMDSs (Zhang et al, ) are interpreted to be the consequence of Phase 4b activity from a large‐volume dike. Earlier phases of the eruption emplace long volatile‐free lava flows.…”
Section: Consequences For Observed Volcanic Featuresmentioning
confidence: 99%